DOSE MORTALITY RESPONCES OF BLISTER BEETLES AGAINST SOME INSECTICIDES - P. SHENDE, SARIKA (The Bioscan, 2013)
In view of significant damage potential of adult blister beetles, dose mortality response for number of insecticides was evaluated to find out efficacious alternative for management of blister beetles. The experiments were conducted at Insect Toxicology Laboratory, Department of Agricutural Entomology, Dr. Panjabrao Deshmukh Krishi Vidyapeeth, Akola (Maharashtra). The insecticides viz., chlorpyriphos 50 EC + cypermethrin 5 EC (0.1375%), lambda cyhalothrin 2.5 EC (0.00375%), alphamethrin 20 EC (0.05%), cypermethrin 10 EC (0.01%), fenvalerate 20 EC (0.02%) and deltamethrin 2.8 EC (0.0042%) at field dose inflicted 100 per cent mortality, within 24 hours. The data on relative toxicity revealed that lambda cyhalothrin 2.5 EC, deltamethrin 2.8 EC and cypermethrin 10 EC were 188.3, 113.0 and 56.5 times more toxic with reference to chlorpyriphos dust, respectively. The order of toxicity based on LC50 values for insecticides under evaluation was lambda cyhalothrin (0.06 ppm) > deltamethrin (0.1 ppm) > cypermethrin (0.2 ppm) > alphamethrin (0.4 ppm) > fenvalerate (0.6 ppm) > chlorpyriphos + Cypermethrin (0.8 ppm) > methyl parathion dust (1.1 ppm) > fenvalerate dust (3.0 ppm) > chlorpyriphos dust (11.3 ppm). Lower LT50 values at 103 dilutions was recorded in cypermethrin (10.0h) and chorpyriphos + cypermethrin (13.0h). In case of dust formulations, minimum LT50 value was recorded with methyl parathion (83.1h), whereas, fenvalerate dust (109.2h) registered highest value. Similar, efficacy trend based on LT50 values was recorded at 104 dilutions. Synthetic pyrethroids proved efficient in inflicting mortality quickly and at lower dose, thus, suggesting their potential in management of blister beetles.